(3SfG GdfjQjf aj EYLGR GdBjI hGdBjJjf hZUf GdQjGV Gdeci aj GdMOjK GdbOSis - (3YHO GdZfj Hf TGcQ Hf eMeO GdSGOGJ GdOeTbj GdMfaj,J (B1265 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd gPg QSGdI UZjQI GdMLe hdPG SejJgG s
(3BNQgG (B:s
(3ddWGdH eWdH hEdi gfG fVH Qjb Gdbde s
(3GdfSNI HgG MhGTs
(3HBNQgG JbQjXs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B33 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B274s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdHdGZIs